Sex differences during the course of diet-induced obesity in mice: adipose tissue expandability and glycemic control - Medrikova, D; Jilkova, Z M; Bardova, K; Janovska, P; Rossmeisl, M; Kopecky, J (International journal of obesity (2005), 2012)
OBJECTIVE: Adverse effects of obesity on glucose homeostasis are linked to low-grade adipose tissue inflammation and accumulation of lipids in non-adipose tissues. The goal of this study was to evaluate the role of adipose tissue plasticity in a less severe deterioration of glucose homeostasis in females compared with males during the course of high-fat (HF) feeding in mice. DESIGN: Mice of the C57BL/6N strain were fed either a chow or obesogenic HF diet for up to 35 weeks after weaning. Metabolic markers and hormones in plasma, glucose homeostasis, adipocyte size and inflammatory status of gonadal (gWAT) and subcutaneous (scWAT) adipose depots and liver steatosis were evaluated at 15 and 35 weeks of HF feeding. RESULTS: HF-fed males were heavier than females until week ∼20, after which the body weights stabilized at a similar level (55-58 g) in both sexes. Greater weight gain and fat accumulation in females were associated with larger adipocytes in gWAT and scWAT at week 35. Although adipose tissue macrophage infiltration was in general less frequent in scWAT, it was reduced in both fat depots of female as compared with male mice; however, the expression of inflammatory markers in gWAT was similar in both sexes at week 35. In females, later onset of the impairment of glucose homeostasis and better insulin sensitivity were associated with higher plasma levels of adiponectin (weeks 0, 15 and 35) and reduced hepatosteatosis (weeks 15 and 35). CONCLUSIONS: Compared with males, female mice demonstrate increased capacity for adipocyte enlargement in response to a long-term HF feeding, which is associated with reduced adipose tissue macrophage infiltration and lower fat deposition in the liver, and with better insulin sensitivity. Our data suggest that adipose tissue expandability linked to adiponectin secretion might have a role in the sex differences observed in obesity-associated metabolic disorders.
Keywords: Weight Gain; lipidy; glukózový toleranční test; Obesity; krevní glukóza; imunohistochemie; sexuální faktory; Elasticity; myši inbrední C57BL; mužské pohlaví; Mice; Diet, High-Fat; hmotnostní přírůstek; dieta s vysokým obsahem tuků; Lipids; pružnost; Blood Glucose; Immunohistochemistry; ženské pohlaví; zvířata; Sex Factors; biologické markery; Adipose Tissue; myši; obezita; Biomarkers; Female; Glucose Tolerance Test; tuková tkáň; Mice, Inbred C57BL; Male; Animals